Perancangan Sistem Informasi Rekam Medis Di Rumah Sakit Pita Insani Siantar - Yudica Rosalina; Kesawa Sundarsih (Journal of Innovative and Creativity (Joecy), 2026)
The patient medical record information system at Vita Isani Siantar Hospital is a system that aims to manage patient data that registers for treatment until the patient leaves the hospital within a certain period of time. In this case, the information system is very important to be designed to prevent errors in the implementation of registration procedures and data processing so that it can be used optimally. The design of the patient medical record information system aims to create a patient medical record information system at Vita Insani Siantar Hospital using computer programs, namely PHP and MySQL in order to facilitate the registration process and create a recapitulation of patient visit reports. In designing the patient medical record information system at Vita Insani Siantar Hospital, the System Development Life Cycle method is used, which consists of system planning, system analysis, conceptual system design, system selection evaluation, functional system design, and system implementation. The design of this system produces a patient recording application until the patient leaves the hospital consisting of three forms, namely a recapitulation report of inpatient and outpatient visits every month and a recapitulation report of the highest annual patient visits. The design of a patient medical record information system at Vita Insani Siantar Hospital is expected to facilitate the process of recording patients and making reports at the hospital so that the hospital can produce accurate data.